EXTRACTION OF FUNCTIONALLY ACTIVE COLLAGEN FROM SALMON FISH AS FORMULATION OF CLAY MASK - CHRISTINE ULINA TARIGAN; WENNY PINTA LITNA TARIGAN (BEST Journal (Biology Education, Sains and Technology), 2022)
The skin of salmon (Oncorhynchus nerka), a by-product of the fillet process line, could serve as an excellent source of aquatic collagen. It was possible to apply active collagen from salmon fish as well as the formulation of clay mask material. Collagen helped in the regeneration and replacement of dead and old cells for improving skin texture and integrity to maintain young and healthy skin. The purpose of this study was to find out which formulations produced the superior physical properties of salmonid collagen clay masks. Extraction of salmon skin purity was conducted by conventional extraction process. Salmon rind was pretreated with 0.5 M acetic acid. The collagen subunits extracted were then analyzed on sodium dodecyl sulfate-polyacrylamide gel (SDSPAGE) to determine the peptide chains. The collagen yield of the conventional method was 35.6%. The soluble collagen was extracted as a raw material for cosmetic material such as clay masks. Clay mask formulations contained collagen as a key ingredient due to their significant advantages as natural moisturizers. The best formulation of salmonid collagen clay mask was an F3 preparation with a kaolin concentration of 25% and a bentonite concentration of 1%.  F3 preparation was more preferred by respondents with good resulting odor, color, and texture parameters.Keywords: Clay, Collagen, Cosmetics, Extract, Salmon, Mask